The economic essence of labor resources and theoretical foundations of their effective management - Dinora Atamurot qizi Haydarova (THE INNOVATION ECONOMY, 2026)
This article provides a theoretical analysis of the economic essence of labor resources and their role in the socio-economic development of the country. The main approaches to the effective use of labor resources, the factors influencing the formation and development of human capital, as well as the modern theoretical and methodological foundations of labor resource management are highlighted. The article reveals structural changes in the labor market, mechanisms for increasing the level of employment, and the economic significance of enhancing labor productivity.